Entrepreneurship Education, Psychological Cognition, and Entrepreneurship Activities: An Analysis Based on a Fuzzy-Set Qualitative Comparative Analysis - Jiang, Yujia; Li, Guobiao; Cai, Xu; Yang, Zihan; Huang, Yangjie; Zhang, Ling; Huang, Leilei (Frontiers in Psychology, 2021)
At present, research in the field of college students’s entrepreneurship is very rich, but the extent to which entrepreneurial education currently affects the entrepreneurial level of college students ; whether it can make graduates more efficient entrepreneurs and other issues remain unclear. We take 187,914 undergraduate and junior college students from 1,231 colleges and universities in China as a sample and use fuzzy-set qualitative comparative analysis (fsQCA) to explore the relationship among five conditions in the entrepreneurial education environment and cognitive level (i.e., the quality of staff, subject curriculum, entrepreneurial competition, intentions, and opportunity identifications) and entrepreneurial activities. The fsQCA results show that none of these factors are sufficient for entrepreneurial activity. Contrarily, a special combination of the five conditions can produce high entrepreneurial activity, as well as substitution and complementarity among the various elements within the configuration. These results show that the combined effect of the five conditions is more conducive for the entrepreneurial activities of college students. Finally, after a discussion of the study’s findings, theoretical and practical contributions are analyzed with regard to the field of entrepreneurship in Chinese colleges, and alternative options are pointed out that college students are more likely to become entrepreneurs in the future.